Analysis of Restitution Coefficient Value on the Ball Using Tracker Software by Utilizing Video Based Laboratory - Delia Achadina Putri; Dandan Luhur Saraswati (Postgraduate, University of Mataram, 2024)
Performing experimental activities in a laboratory using the available equipment is not as straightforward as it may seem. In practice, conducting experiments can be challenging, and various factors can contribute to erroneous measurement results. One such factor is systematic errors, which occur due to inaccuracies in the measurement tools used. Additionally, error sources from external factors can also influence the measurement results. It is important to be aware of these potential errors and take appropriate measures to minimize their impact during experimental procedures. Tracker software is a valuable tool that can enhance the accuracy of experimental activities conducted in laboratories. This software assists in generating more precise data by tracking and analyzing various elements of the experiment. By utilizing tracker software, researchers can closely monitor the movement and behavior of objects, making it easier to measure and record data accurately. This technology plays a significant role in improving the reliability and efficiency of experimental procedures in the laboratory setting. From the study's objectives, it can be deduced that the restitution coefficient values obtained through manual data collection for the bekel ball are ð‘’ = 0.5136 Â± 0.004214, and for the ping pong ball, it is ð‘’ = 0.4566 Â± 0.01736. On the other hand, when using tracker software for data collection, the restitution coefficient value for the bekel ball is ð‘’ = 0.5397 Â± 0.0008731, and for the ping pong ball, it is ð‘’ = 0.5115 Â± 0.001154.